PERAN IBU RUMAH TANGGA DALAM PENANGANAN HIPERTENSI - Devangga Darma Karingga; Agnes, Yeni Lufiana Novita; Rahayu, Kun Ika Nur; Wahdi, Achmad; Suharto, Idola Perdana Sulistyoning; Alimansur, Moh (Stikes Yarsi Mataram, 2025)
Hypertension is one of the most common non-communicable diseases and often goes undetected until it leads to serious complications. In Indonesia, the prevalence of hypertension reaches 34.1%, with most sufferers unaware of their condition. Low awareness and limited family skills-especially among housewives-in managing hypertension is a major contributing factor. This community service activity aimed to improve the knowledge and skills of housewives in managing hypertension within the family setting. The program was implemented in Banyakan Village, Kediri Regency, involving 15 housewives as participants. The methods included socialization, education on hypertension, training on preparing low-sodium menus based on the DASH diet, and the introduction of simple relaxation techniques. Pre-test and post-test evaluations showed an increase in average scores from 46.7 to 80.7. Furthermore, all participants stated that the program was beneficial and enriched their understanding. These results indicate that family-based education is effective in supporting hypertension control. This initiative is expected to contribute to the adoption of healthy lifestyles within families and support national programs such as GERMAS.